Design of typical welded connections using BS5950-1:2000 and Eurocode 3 - Koh, Cheryl Yu Jia. (2011)
This paper involves the design aspects of joints, in particular, the design of typical welded connections based on BS5950-1:2000 and Eurocode 3. The objective is to demonstrate the key differences in the structural design of typical welded connections by comparing extensively the design procedures using both BS5950-1:2000 and Eurocode 3 and evaluate on their key differences that are generally in terms of equations, parameters, terminology and symbols. Emphasis in this study is placed on the design of one of the most common form of welded connections, which is the fillet weld connection. An overview is given on the general approach of both BS5950-1:2000 and Eurocode 3 being based on limit state principles using partial safety factors. Through this study, the UK Standard Code of Practice that produces more conservative and cost-optimizing steel construction would be discussed.